Spatial Thinking dalam Pembelajaran Geografi di Era Digital 4.0 dalam Persfektif Filsafat Pendidikan - Ika Listiqowati (Jurnal Pendidikan Geosfer, 2025)
The Digital Era 4.0 brings good fortune but also challenges. Every aspect of life is connected to the internet, digital technology is connected without time and space limitations. Facing this requires spatial thinking skills because spatial thinking is a complex thinking skill that includes knowledge, skills, attitudes, and ways of thinking with spatial concepts. Spatial thinking is one of the skills achieved in geography learning. The problem is that geography learning in general is not all oriented towards spatial thinking skills but is still oriented towards mastering concepts and theories. This article aims to provide education through the perspective of educational philosophy that spatial thinking needs to be mastered by students through geography learning as an adaptation to the Digital Era 4.0. In the perspective of educational philosophy, spatial thinking in geography learning in the Digital Era 4.0 is seen from ontology, epistemology and axiology. Ontology is the essence of a science, epistemology is related to the method by which science is obtained, axiology is the utility value/role of a science. Abstrak Era Digital 4.0 memberikan keberuntungan namun juga tantangan. Setiap sendi kehidupan berhubungan dengan internet, teknologi digital terhubung tanpa batasan waktu dan ruang. Menghadapi hal ini perlu keterampilan spatial thinking sebab spatial thinking merupakan keterampilan berfikir yang kompleks meliputi pengetahuan, keterampilan, sikap, dan cara berfikir dengan konsep keruangan. Spatial thinking adalah salah satu keterampilan yang dicapai dalam pembelajaran geografi. Masalahnya pembelajaran geografi secara umum belum semua berorientasi pada keterampilan spatial thinking namun masih berorientasi pada penguasaan konsep dan teori. Artikel ini bertujuan memberikan edukasi melalui persfektif filsafat pendidikan bahwa spatial thinking perlu dikuasai siswa melalui pembelajaran geografi sebagai adaptasi terhadap Era Digital 4.0. Dalam persfektif filsafat pendidikan, spatial thinking dalam pembelajaran geografi di Era Digital 4.0 dilihat dari ontologi, epistemologi dan aksiologi. Ontologi adalah hakikat dari suatu ilmu, epistemologi berkaitan dengan metode bagaimana ilmu itu diperoleh, aksiologi adalah nilai guna dari suatu ilmu.